The Role of BAFF-R Signaling in the Growth of Primary Central Nervous System Lymphoma - Zhou, Xiaolan; Mulazzani, Matthias; von Mücke-Heim, Iven-Alex; Langer, Sigrid; Zhang, Wenlong; Ishikawa-Ankerhold, Hellen; Dreyling, Martin; Straube, Andreas; von Baumgarten, Louisa (Frontiers in Oncology, 2020)
Primary CNS lymphoma (PCNSL) is an aggressive brain tumor. Despite improvements in therapeutic algorithms, long-term survival remains rare, illustrating an urgent need for novel therapeutic targets. BAFF-R is a pro-survival receptor expressed on most malignant B cells, including PCNSL. To date, its role in PCNSL growth remains elusive. Here, we created a BAFF-R knockout lymphoma cell line (BAFF-R-KO) using CRISPR-Cas9. In serum-starved conditions, BAFF-R-KO cells exhibit decreased viability in vitro compared to BAFF-R+ cells. Combining an orthotopic mouse model of PCNSL with chronic cranial windows and intravital microscopy, we demonstrate a significant delay in tumor growth in mice inoculated with BAFF-R-KO cells compared to BAFF-R+ PCNSL. Additionally, median survival of BAFF-R-KO mice was significantly prolonged. Altogether, our results indicate the high potential of BAFF-R as a novel treatment target for PCNSL.